Intersectoral Convergence and ICTs: Integrated ICT Approaches to Rural Poverty Reduction - Nirupam Bajpai; Abhishek Beriya; John Biberman; Anchal Sharma; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
As reforms have paved the way for India's rapid economic expansion in recent years, particularly in the service sector, Information and Communications Technology (ICT) has assumed a dominant role as the underwriter of India's growth. Outside of the commercial applications where ICT has been most extensively applied so far, ICT also holds great potential to drive human development, narrowing gaps between the rich and the poor as well as rural and urban areas. In many development-adjacent sectors, particularly education, agriculture, and health, platforms and initiatives have already demonstrated ICT's promise as a transformational suite of technologies which democratize information and dramatically reduce transaction costs. However, even greater progress is possible if initiatives apply an intersectoral approach which applies best practices from other sectors, highlights synergies between sectors, and identifies pitfalls stemming from hidden competition of priorities between sectors that could otherwise derail a project. Intersectoral analysis also recognizes how advances in the sectors under study contribute to growth in the broader economy. By applying an intersectoral lens, individual programs can be strengthened, new opportunities can be identified, and ICT can be more thoroughly woven into a tapestry that benefits all aspects of people's lives. ICT-driven development has not entirely ignored intersectorality, but opportunities abound for improving these initiatives by applying a more holistic lens. In particular, the field of nutrition is most sorely in need of mainstreaming within the many different siloed development objectives that touch upon it. Data, the foundation of ICT, provides great opportunities for refining programs of all types, but also carries great risks to privacy and potentially social equality. And untapped synergies exist between the cutting-edge advances in the Education sector and educational initiatives in other sectors which have not benefited from the same intentional pedagogical design.
Keywords: 330